Entrepreneurial Urbanism in India : The Politics of Spatial Restructuring and Local Contestation - Smitha, Kanekanti Chandrashekar (Springer Singapore : Imprint: Springer, 2017)
Through the analysis of Indian metropolises, this volume critiques the reality of "entrepreneurial governance" that has emerged as a major urban development practice in cities of the global south. In neoliberal India, the use of management rhetoric in urban development has rapidly led to the growth of urban/peri-urban structures and spaces that are supposedly "smart" and "entrepreneurial", which are networked within global systems of production, finance, technology/ telecommunication, culture and politics. Through diverse empirical evidence from India, particularly from the metropolises of New Delhi, Mumbai, Bengaluru and Chennai, this volume focuses on the fallout of the deployment of "entrepreneurial governance" practices at national, state and local levels. Foremost, it explores the impact of specific institutional and organizational reorientations and changing urban spatial landscapes at the local level; secondly, it discusses the socio-economic implications of rollback of the state and involvement of non-state organizations in governance as part of urban entrepreneurialism; further, it discusses the regulation of urban development projects by local governments and the impact of "entrepreneurial governance" for citizens, often resulting in social exclusion and inequality. Finally, it explores the inherent contradictions within political and institutional landscapes that can be described as "entrepreneurial". Written by scholars from diverse disciplinary backgrounds, and focusing on different facets of entrepreneurial governance in Indian metropolises, this book is of interest to researchers of urban politics, public policy, urban sociology, anthropology, urban geography, planning and architecture.
Keywords: Social sciences.; Urban geography.; Urban economics.; Sociology, Urban.; elektronické knihy; electronic books